Soils as proxies of the history of landscape and climate: Examples from eastern Bhutan - Dorji, Karma Dema; Bliumler, Rupert (Journal of Nepal Geological Society, 2013)
The reconstruction of the landscape history and past environmental fluctuations is a major task with respect to forecasting man or naturally-induced changes. In this context the extent of soil development in fluvial deposits of the Chamkhar Chhu river system in Eastern Bhutan were studied for relative age dating. The deposits represent 25 fluvial terraces up to more than 260 m above the recent river level. We used a set of methods covering physical (soil texture, specific surface area) and chemical (pedogenic oxides, soil development indices) processes, and we calculated solum-weighted means of individual soil parameters to compare different sites, and to minimize problems caused by heterogeneity of the parent materials. The results were maintained by numerical age dating of fossil A horizons. Pedogenic oxides and soil development indices as well as soil texture indicate that soils can be used as proxies of the history of landscape and climate. Local as well as global climate fluctuations are well preserved in the soils despite slope processes inducing reverse-tended soil formation in fluvial deposits of Late Pleistocene origin and older, while soils on fluvial deposits of Holocene age indicate distinct chronosequences (Dorji et al. 2009).